eTu{d,b}e: DEVELOPING AND PERFORMING SPATIALIZATION MODELS FOR IMPROVISING MUSICAL AGENTS (Proceeding of the International Conference on Arts and Humanities, 2024)
The eTube is a simple acoustic instrument outfitted with a microphone and a two-button controller which we program to facilitate interaction between an improviser and improvising musical agents. Through an iterative research-creation process, we develop and perform various etudes with the eTube and musical agents, generating new knowledge through musical creation. Through this process, we have developed two interactive spatialization systems for the eTube.We begin by describing the eTu{d,b}e framework which refers to the eTube instrument and a series of improvised etudes based on human-computer musical interactions. An overview of the instrument is presented, as well as the existing systems as they were when Pocius began the spatialization portion of this project. Secondly, we outline two interactive spatialization systems designed for improvised performance with the eTube and musical agents. An overview of the updates made to the eTu{d,b}e framework is presented, followed by a description of the two spatialization systems. Finally, six different performances are presented as case studies to emphasize the advancements and challenges of the project as new approaches are developed.
Keywords: Musical agents; augmented instrument; improvised performance; Spatial Audio